Knowledge about the COVID-19 and ways of its prevention among Medical University of Warsaw students - Katarzyna Lewtak; Anna Poznańska; Katarzyna Okręglicka; Krzysztof Kanecki; Magdalena Bogdan; Aneta Nitsch-Osuch (Nofer Institute of Occupational Medicine, 2022)
Background The aim of the study was to assess the state of knowledge of Medical University of Warsaw (MUW) students on COVID-19, modes of transmission and preventive measures. Material and Methods The study was conducted in October 2020. The participants were all the students attending classes at MUW - 8922 persons. All had completed the online training "Work safety and hygiene during COVID-19." To assess their state of knowledge an online questionnaire was made available on the MUW e-learning platform. The questionnaire comprised 4 parts: (1) awareness of rules of hand hygiene, (2) medical aspects of COVID-19, (3) preventing SARS-CoV-2 infection transmission in health care facilities, and (4) preventing infection transmissions in the society. Results The majority of students (93.9%) demonstrated a sufficient level of knowledge. The highest passing threshold was found on the medical programme (96.7% of students with satisfactory level of knowledge), dentistry (96.2%) and pharmacy (95.5%). The statistically significant factors that differentiated student results proved to be faculty (p < 0.001), study programme (p < 0.001), year of studies (p = 0.001), form of studies (p < 0.001). The participants most often showed full knowledge (100% correct answers in sub-area) of preventing infection transmissions in the society (93.3%) and medical aspects of COVID-19 (91.8%), less complete in terms of ways of preventing infection transmission in health care facilities (85.4%), and in particular hand hygiene rules (78.3%). All the variables characterizing academic status (study programme, faculty, year and form of studies) were statistically significant differentiating factors for students' full knowledge in all of the 4 analyzed sub-areas, while students' sex only in the sub-area of COVID-19 medical aspects. Conclusions There is a clear need for conducting systematic educational activities among students of all medical study programmes and assessing their level of knowledge in those areas that were identified as least frequently controlled, namely, hand hygiene and infection transmission in health care facilities. Med Pr. 2022;73(5):369-81